KONTRIBUSI END - USER COMPUTING SATISFACTION TERHADAP KEPUASAN PENGGUNA WEBSITE PORTAL AKADEMIK PADA SISTEM SMART CAMPUS UNIVERSITAS NEGERI PADANG - Lovri Dahliana; Zulhendra Zulhendra; Ahmaddul Hadi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This study was conducted to reveal the contribution of End - User Computing Satisfaction ( EUCS ) to the satisfaction of the end users in the UNP Academic Portal website. This research is a descriptive correlational ex post facto nature. The sample in this study amounted to 100 students. Groups as well as proportional (Proportionate Stratified Random Sampling). Data on the number the number of end-user portal website Academic Computer Center was obtained from the head of the UNP, EUCS which are factors such as the content, accuracy, format, easy of use, timeliness which become variables in this study were collected through a questionnaire using a Likert scale that has been tested for validity and reliability. Then the data were analyzed using statistical methods to analyze the impact. The results of data analysis showed : Content variables, Accuracy, format, Easy of use and Timeliness together accounted for 92,70 % of user satisfaction Portal website academic in the UNP.  So it can be concluded factor content, accuracy, format, easy of use, timeliness has contributed to user satisfaction UNP Academic Portal website, if the quality of the website Portal Academic UNP in view of the five factors of content, accuracy, format, easy of use, improved timeliness then the end-user satisfaction Academic Portal website that faculty and students will also be increased. Keywords        : Academic Portal website, Content, Accuracy, format, Easy of use, Timeli ness, satisfaction end-user.